“Estudio comparativo de la prescripción de la acción y de la pena en el código penal y COIP del Ecuador”. - Carvajal Medina, Paúl Jonathan (2017)
The present research is divided into four chapters. The first chapter presents the introduction, the frame of reference, the approach to the problem, the general and specific objectives, and a discussion detailing the feasibility and origin of the investigation. In the second chapter, the theoretical framework is presented and information is presented on a comparative research study regarding crimes, penalties, and sanctions and the issues of rules and time in each area of concern. This project is divided into three units. Unit I covers the main theme and the prescriptions and subdivisions relative to the issue of penalty. Unit II examines the issues of time and action relative to particular crimes. Unit III presents the issues of time and penalty in crimes and their relationship to contraventions typified in the Penal Code and that are currently found in the COIP. The third chapter discusses the methodological framework of the research study and presents the qualitative, deductive, analytical, historical, descriptive, explanatory, longitudinal, and comparative methods used in the study. The fourth chapter presents the administrative framework and the conclusions and recommendations of the study